1990
DOI: 10.1254/jjp.52.587
|View full text |Cite
|
Sign up to set email alerts
|

Detrusor hyperreflexia induced by intravesical instillation of xylene in conscious rats.

Abstract: Abstract-Intravesical instillation of xylene (30-50%) produced detrusor hyper reflexia characterized by a decrease in both the bladder capacity (time to micturition in the cystometrogram) and the urine volume in conscious rats placed in a restraining cage. At this time, the bladder tissue showed evidence of experimental cystitis with degradation of the epithelium and edema and hemorrhage in the submucosa, and a slight increase in the content of prostaglandin E2, which stimulates directly and/or indirectly caps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
6
1

Year Published

1999
1999
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 15 publications
(22 reference statements)
3
6
1
Order By: Relevance
“…Therefore, acetone can easily penetrate bladder tissue and may injure seriously the lamina propria compared with xylene. Actually, in contrast with the photograph of xylene-treated bladder, which was investigated by Morikawa et al [1990], acetone-induced hemorrhage and impairment in the lamia propria in our study.…”
Section: Discussioncontrasting
confidence: 76%
See 1 more Smart Citation
“…Therefore, acetone can easily penetrate bladder tissue and may injure seriously the lamina propria compared with xylene. Actually, in contrast with the photograph of xylene-treated bladder, which was investigated by Morikawa et al [1990], acetone-induced hemorrhage and impairment in the lamia propria in our study.…”
Section: Discussioncontrasting
confidence: 76%
“…Intravesical instillation of a chemical agent, such as ether solution or formalin, is also known to cause chemical cystitis in human [Nellans et al, 1978;Gattegno et al, 1988;Fair, 1974]. In rats, it was reported that intravesical administration of xylene, a chemical irritant, and intraperitoneal injection of cyclophosphamide induced chemical cystitis and caused a decrease in bladder capacity [Maggi et al, 1988[Maggi et al, , 1992Morikawa et al, 1990]. Acetone, an organic solvent, has been known to remove the glycosaminoglycan layer of the bladder transitional uroepithelium [Ruggieri et al, 1985[Ruggieri et al, , 1986Levin et al, 1990].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, whether injury or inflammation in the uterus may sensitize the activity of the lower urinary tract in a cross-organ manner via the overlapping neural pathways within the nervous system is an interesting question that requires further elucidation. Our laboratory recently demonstrated a windup-like spinal reflex potentiation (40,41) that the strength of the pelvic-urethra reflex activity was dynamically potentiated by repetitive afferent inputs and it was presumed that this windup-like spinal reflex potentiation may be involved in postinflammatory hyperalgesia of the lower urinary tract (18,22,49,50) or chronic pelvic pain syndrome characterized by urogenital pain (58). Thus, the first purpose of this study is to test whether there is a cross-sensitization between an irritated uterus and the spinal pelvic-urethra reflex activity as well as to see the response of lower urinary tract.…”
mentioning
confidence: 99%
“…Prostaglandins (PGs), produced from COX‐induced metabolism of arachadonic acid, are known to play roles in the regulation of the micturition reflex. PGs are released from the bladder in response to a variety of stimuli, including distension, pelvic nerve stimulation (Khalaf et al ., 1979) and chemical irritation (Morikawa et al ., 1990). These locally produced PGs have been suggested to modulate bladder afferent nerve activity (Maggi, 1992; Wibberley, 2005).…”
Section: Introductionmentioning
confidence: 99%